Evaluation of Drug Storage Using FIFO/FEFO Methods In Royal Prima Medan Hospital Pharmacy Installation - Sri Rezeki, Dewi; Girsang, Ermi; Silaen, Mangatas; Nasution, Sri Ramadhani (International Journal of Health and Pharmaceutical (IJHP), 2022)
The inappropriate drug storage system can cause the drug to break down quickly, drug expiration, stockout, and drug stagnation. This study aims to evaluate the storage of drugs using the FIFO and FEFO methods in the Royal Prima Medan Hospital Pharmacy Installation Warehouse. This type of research is descriptive qualitative. The research samples were employees of Royal Prima Medan Hospital Pharmacy Installation Warehouse who had worked for ± 1 year. For the validity and reliability of the data, source triangulation and method triangulation were used. Data analysis in this study used domain analysis. The results of this study indicate that drug storage activities using the FIFO and FEFO methods in Royal Prima Medan Hospital Pharmacy Installation Warehouse have been running well. Although in the implementation of drug storage activities, human resources problems have been found that play a dual role in their duties, problems of miscommunication among human resources and there is still a lack of training on drug storage using the FIFO and FEFO methods. It is hoped that the Royal Prima Medan Hospital Pharmacy Installation warehouse will more attention to existing human resources problems.